(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The aim of the study is to study how to use the marketing dimensions of sensory marketing in its dimensions (visual marketing, taste marketing, tactile marketing, marketing of audio, audio marketing) and the impact on customer behavior patterns (one-dimensional) He was asked the following questions: What is the perception of the employees of the first class restaurants in the holy province of Karbala on the concept and dimensions of sensory marketing What are the most important dimensions of sensory marketing according to the perception of the study sample? 3. What is the perception of the employees of the first class restaurants in the holy province of Karbala about the behavioral patterns of customers and the level of diagnosis? Are the employees of the first class restaurants in the holy city of Karbala aware of the level of relationship between the sensational marketing and behavioral patterns of customers? Is this awareness based on digital indicators reflecting the reality of the situation. Five of the first class restaurants were selected in Karbala governorate for the purpose of conducting field research, namely Sultan Corner Restaurant, Dar Nasrawi Restaurant, Al Shalal Restaurant, Rehana Restaurant and Rotana Hotel Restaurant. (62) questionnaires were useful for statistical analysis (51) questionnaire. In order to achieve these objectives, the research was based on a set of hypotheses, the most prominent of which is: There is a significant correlation relationship between sensory marketing and behavioral patterns For customers,. There is a significant effect of sensory marketing in the behavioral patterns of customers. The researcher reached a number of conclusions, the most important of which is that the term mainly simulates the five senses of customers with the aim of arousing them and motivating them towards the products provided by marketers. In addition, the identification of behavioral patterns of customers is an unavoidable necessity because they And the nature of purchasing decisions as well as the extent of attachment and attendance of the organizations and shops that he always visits, and is determined accurately according to a range of internal factors that relate to the same customer and external, which relate to the environment surrounding the customer. Finally, the researcher is recommended to enhance attention to the dimensions of sensory marketing and to guide the attention of restaurant employees to the research sample to stimulate and stimulate customer senses through the senses (sight, taste, smell, hearing and touch). Relational ties with customers through the management of marketing emotions and personal analysis of the customer